Манипулирование с доставленным грузом у ос-полистов (Hymenoptera, Vespidae) - Русина, Л.Ю. (Вестник зоологии, 1999)
Исследованы 3 вида полистов, обитающих в Херсонской обл.: Polistes dominulus Christ, P. nimpha Christ, и P. chinensis F. Проведен анализ цепей актов поведения при строительстве гнезда и кормления личинок. Сравнивали 3 типа манипуляций с доставкой груза: 1. Фуражир сам использует всю порцию для кормления личинок; 2. Отдает часть порции другой особи; 3. Отдает всю порцию. У всех видов соотношение этих типов манипулирования было разным в 1997 и 1998 гг. Рабочие особи передавали одна другой только еду. Все случаи передачи древесной пульпы были связаны с агрессивными действиями самки-основательницы. Зарегистрированы также межвидовые отличия в соотношении форм манипуляций и в характере строительного поведения. Эти данные могут быть использованы при анализе эволюции полиетизма общественных ос. Polistes dominulus Christ, P. nimpha Christ, and P. chinensis F. were studied in the Kherson region, Ukraine. The analysis of foragers’ behaviour after the load delivery was conducted. Three types of task partitioning were compared: 1. Forager keeps the load and uses it herself at the nest. 2. Forager transfers part of the load to nestmates, but retains a portion which she uses herself. 3. Forager transfers the entire load to nestmates. All the species demonstrated the difference in degree of task partitioning in 1997 and 1998. The workers usually transferred food but not pulp. All the cases of the pulp transfer occurred if the queen took away the pulp from the foragers aggressively. Interspecific differences in degree of task partitioning and in workers building behaviour were found. The received data can be used in the analysis of the evolution of social wasps polyethism.